2018
DOI: 10.1155/2018/7560707
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Obesity-Linked FTO rs9939609 Variant on Physical Activity and Dietary Patterns in Physically Active Men and Women

Abstract: Single nucleotide polymorphisms (SNPs) in the fat mass and obesity-associated (FTO) locus are associated with obesity, but lifestyle factors may modulate the obesity risk related to FTO. This study examined the physical activity and dietary patterns of 528 physically active white men and women (mean (SD): 34.9 (9.5) years, 26.6 (4.3) kg·m−2) carrying different risk variants of FTO SNP rs9939609. Sex, age, and anthropometric measurements (stature, body mass, and waist circumference) were self-reported using an … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…In an attempt to understand the mechanism of FTO obesity modulation, it was suggested that an individual's behavior toward food consumption is primarily regulated by this SNP. In fact, it suggests that A/A homozygous is more likely to be responsible for the reduction of personal ability to perform regular activity [43]. The A allele was reported as the risk allele [12], which is consistent with the present study.…”
Section: Discussionsupporting
confidence: 92%
“…In an attempt to understand the mechanism of FTO obesity modulation, it was suggested that an individual's behavior toward food consumption is primarily regulated by this SNP. In fact, it suggests that A/A homozygous is more likely to be responsible for the reduction of personal ability to perform regular activity [43]. The A allele was reported as the risk allele [12], which is consistent with the present study.…”
Section: Discussionsupporting
confidence: 92%
“…The genomic inflation coefficient (lambda) for the obesity cohort was computed as 1.05. We also include eight SNPs found slightly above the significance threshold in the FTO gene that are reported in several studies as obesity-related (Ehrlich and Friedenberg 2016;West et al 2018). In comparison to the two quantitative-trait BMI GWASs, this study identified several more associations around the NEGR1 gene on chromosome 1.…”
Section: Gwas Of Bmi In the Healthy Nevada Cohortmentioning
confidence: 98%
“…Hakanen et al [25] demonstrated no association between FTO genotype and energy intake or physical activity. However, West et al [10] reported that individuals with the A allele reported higher total and vigorous physical activity levels compared with TT individuals. In contrast, at the three-year follow-up, we found that TT individuals reported a higher vigorous physical activity level than both AA and TA individuals, and a higher total physical activity level than the TA individuals.…”
Section: Discussionmentioning
confidence: 98%
“…Celis-Morales et al [9] demonstrated that physical activity attenuates the effect of FTO on BMI and waist circumference. West et al [10] described that individuals with the A allele had higher physical activity levels than individuals with TT alleles despite similar adiposity-related measures.…”
Section: Introductionmentioning
confidence: 99%